Programming Microsoft Dynamics 365 Business Central : Build customized business applications with the latest tools in Dynamics 365 Business Central, 6th Edition /: Build customized business applications with the latest tools in Dynamics 365 Business Central, 6th Edition. (2019) - Brummel, Mark; Studebaker, David; Studebaker, Chris
No abstract available